Parental negative affect and postnatal depressive symptoms: Associations with infant negative affect - Kukkonen, Elina (My University, 2019)
Associations between postnatal depression and infant temperament have been studied widely. Also, parental temperament and infant outcomes have been under consideration due to the genetic link between these two and because parental personality is related to higher risk for depression postnatally. However, very few previous studies with a focus on postnatal depression have controlled for parental temperament. This study included a subset of participants (N = 347) from the larger FinnBrain Birth Cohort Study. The aim was to investigate the associations between parental Negative Affectivity, postnatal depressive symptoms and parent-rated infant Negative Affectivity during the first year after birth. Specifically, we examined both maternal and paternal self-reported temperament, parent-reported postnatal depression at 3, 6 and 12 months and parental perceptions of infant temperament at 6 and 12 months of age separately. Results showed that including maternal Negative Affect to the linear regression model attenuated the association between postnatal depression and infant Negative Affect both at 6 and 12 months. However, in paternal models, paternal Negative Affect did not have as strong attenuating effect at 6 months, and at 12 months, both paternal depressive symptoms and paternal Negative Affect had a clear unique association with infant Negative Affect. The results raise questions about the overlap of Negative Affectivity temperament trait and postnatal depression, especially in mothers, and suggests that both should be considered when studying the influence of postnatal depression on ratings of child temperament. However, the findings also indicate that both parent temperament and depression may have unique association with infant temperament especially in paternal data. Clinical implications and future research are discussed.
Keywords: postnatal depression, infant temperament, negative affect, fathers